2009
DOI: 10.1111/j.1472-765x.2009.02591.x
|View full text |Cite
|
Sign up to set email alerts
|

Issues in determining factors influencing bacterial attachment: a review using the attachment ofEscherichia colito abiotic surfaces as an example

Abstract: Summary An understanding of the mechanisms which facilitate the attachment of Escherichia coli and other bacterial species to abiotic surfaces is desired by numerous industries including the food and medical industries. Numerous studies have attempted to explain bacterial attachment as a function of bacterial properties such as cellular surface charge, hydrophobicity and outer membrane proteins amongst others. Conflicting evidence in the literature both for and against a positive relationship may arise from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
100
0
3

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(103 citation statements)
references
References 44 publications
(138 reference statements)
0
100
0
3
Order By: Relevance
“…A positive correlation between the hydrophobic properties of E. coli isolates and their attachment abilities has been reported in some studies (37)(38)(39)(40), whereas others have failed to find such a relationship (41)(42)(43). It has been suggested that the differences between these studies could be explained, e.g., by the number and variety of strains included in the study and/or a lack of sensitivity within methods (35). One aim of the study was to investigate whether the two main virulence factors of STEC, i.e., Stx bacteriophages and the eae gene encoding intimin, could influence the biofilm-producing abilities of E. coli.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A positive correlation between the hydrophobic properties of E. coli isolates and their attachment abilities has been reported in some studies (37)(38)(39)(40), whereas others have failed to find such a relationship (41)(42)(43). It has been suggested that the differences between these studies could be explained, e.g., by the number and variety of strains included in the study and/or a lack of sensitivity within methods (35). One aim of the study was to investigate whether the two main virulence factors of STEC, i.e., Stx bacteriophages and the eae gene encoding intimin, could influence the biofilm-producing abilities of E. coli.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the hydrophobicity of these isolates increased with increasing temperature, whereas the isolates of the other two serotypes displayed low hydrophobicity at all temperatures. The hydrophobicity of a bacterial cell is largely influenced by the residues and structures on the surface of the cell, and it varies between species and strains and even within the same strain depending on the mode and stage of growth and the composition of the growth medium (35). It is not surprising that the surface structures and, thereby, the surface hydrophobicity may vary between isolates of different serotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Curli may be involved in the adherence of SePEC to the mucosal extracellular matrix after fragilization of the epithelium and in the formation of biofilm on organic (not only animals, but also plants) and non-organic surfaces by O157:H7 EHEC and other pathogenic strains. But more studies are needed, especially in vivo to more precisely understand their role in E. coli pathogenicity (Wu and Fives-Taylor, 2001; Barnhart and Chapman, 2006;Goulter et al, 2009;Saldana et al, 2011).…”
Section: The Appendicesmentioning
confidence: 99%
“…For example, O157:H7 differs from K-12 in genome size and outer membrane structure (3,7,9,18,20). Natural isolates of E. coli are genetically highly heterogeneous, and their chromosome sizes vary from 4.5 to 5.5 Mb (18).…”
mentioning
confidence: 99%